Effect of Lavender Powder on Microbial, Physicochemical, Sensory and Functional Properties of Yoghurt - Hale İnci Öztürk; Sümeyye Aydın; Nihat Akın (International Journal of Secondary Metabolite)
The objective of this research was to determine changes in microbial flora and functional properties of yoghurts containing lavender powder at rates of 0.010, 0.025, 0.050 and 0.075%. The effect of lavender powder on the potential flora during fermentation was determined, furthermore, alterations in microbiological properties of yoghurts were examined during the storage period (1 d, 7 d and 14 d). Yoghurt samples containing 0.010, 0.025, 0.050 and 0.075% lavender powder, were coded A1, A2, A3, and A4, respectively. Streptococcal counts were 8.89±0.21, 8.71±0.09, 8.77±0.13, 8.66±0.04 and 8.91±0.13 log CFU/g, respectively, in the control, A1, A2, A3, and A4 samples. No decrease in streptococcal counts was observed during storage in all samples. Lactobacilli counts were 8.58±0.06, 8.43±0.26, 8.34±0.26, 8.02±0.02 and 8.53±0.34 log CFU/g, respectively, in the control, A1, A2, A3 and A4 samples. While the lactobacilli count of the control sample decreased during the storage period, it remained constant in A1, A2, A3 and A4 samples at the end of the storage time. It was determined that the lavender powder supplementation contributed the viability of lactobacilli during storage. No statistically significant difference was found in the total bacterial counts between the samples on the first day, however the highest total bacteria content was determined in A4 sample (8.31±0.01 log CFU/g) at the end of the storage period (14 d).